Problem-Based Learning with Pancasila Smart Board Media: Enhancing Grade 2 Students' Pancasila Education Outcomes at SD 1 Prambanan Lor - Sunaisah, Sunaisah; Maulida, Farida; Maharani, Fara Fatika; Astuti, Nur Kusuma; Masfuah, Siti (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study aims to improve the learning outcomes of second-grade students at SD 1 Prambatan Lor in Pancasila Education through the implementation of the Problem Based Learning (PBL) model assisted by the Pancasila Smart Board media. The learning problems previously encountered include low student interest, monotonous teaching methods, and the lack of concrete media to help students understand Pancasila values in a meaningful way. Research Methods: This research used the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, which was carried out in two cycles. Each cycle consisted of the stages of planning, action, observation, and reflection. Finding/Results: The results showed that applying the PBL model with the support of the Pancasila Smart Board media improved both student activity and learning outcomes. The interactive and visual features of the smart board facilitated a more concrete and enjoyable understanding of the concepts. Conclusion: The combination of the PBL model and Pancasila Smart Board media proved effective in improving the learning outcomes of Pancasila Education among second-grade students.